Development and validation of the (inner) Strength-Based Inventory - Wongpakaran, Nahathai (Mental health, religion & culture, 2020)
Ten perfections (known as inner strengths) are considered positive psychological characteristics, namely, generosity, morality, mindfulness/meditation, wisdom, perseverance, patience and endurance, truthfulness, determination, loving kindness and equanimity. The goal of this study was to develop a new instrument, the (inner) Strength-Based Inventory (SBI) based on these ten perfections. In all, 947 participants completed the SBI for item evaluation using Rasch analysis, and 556 completed the original version of the SBI comprising 10 items with five to eight response choices. The final version comprising 10 items, with five choices for each item, which were completed by 391 participants for the second evaluation. All 10 items showed a unidimensional construct with good fit statistics, good reliability and targeting. The SBI provided sufficient validity and reliability based on the Rasch measurement model. It may facilitate counselling and psychotherapy by enabling clinicians to use it as an individual’s positive resource. Further investigation among diverse cultures is encouraged.